The possibilities for global inequality and poverty reduction using revenues from global carbon pricing - James B. Davies; Xiaojun Shi; John Whalley (The University of Western Ontario, Economic Policy Research Institute (EPRI), 2012)
Global carbon pricing can yield revenues which are large enough to create significant global pro-poor redistributive opportunities. We analyze alternative multidecade growth trajectories from 2015 to 2105 for major global economies with carbon tax rates designed to stabilize emissions in the presence of both continued country growth and autonomous energy use efficiency improvement. In our central case analysis, revenues from globally internalizing carbon pricing rise to 8% and then fall to 6% of gross world product. High growth in India and China reduces global inequality and poverty strongly over time, but important incremental redistributive effects can be achieved using global carbon pricing revenues. Taking into account both between-country effects and previous literature estimates of within-country effects, a global carbon tax alone tends to be regressive in its global incidence. However, if its revenues are redistributed globally via equal per capita transfers, in our central case the Gini coefficient for world income falls by about 3% and the share of the bottom decile rises by 81% on average from 2015 to 2105. The population living in poverty falls by 16% in 2015. Going further, global poverty could be eliminated entirely by 2015 according to our calculations if one third of global carbon tax revenues were redistributed directly to the poorest individuals.
Keywords: O19; Q56; 330; Carbon Pricing; Gini; Poverty Reduction; Millennium Development Goals; Ökosteuer; Verteilungswirkung; Einkommensverteilung; Armutspolitik; Gini-Koeffizient; Umweltbelastung; Szenariotechnik; Welt